2020
DOI: 10.3390/en13092155
|View full text |Cite
|
Sign up to set email alerts
|

A Robust q-Rung Orthopair Fuzzy Information Aggregation Using Einstein Operations with Application to Sustainable Energy Planning Decision Management

Abstract: A q-rung orthopair fuzzy set (q-ROFS), an extension of the Pythagorean fuzzy set (PFS) and intuitionistic fuzzy set (IFS), is very helpful in representing vague information that occurs in real-world circumstances. The intention of this article is to introduce several aggregation operators in the framework of q-rung orthopair fuzzy numbers (q-ROFNs). The key feature of q-ROFNs is to deal with the situation when the sum of the qth powers of membership and non-membership grades of each alternative in the universe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
67
0
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 94 publications
(69 citation statements)
references
References 146 publications
1
67
0
1
Order By: Relevance
“…Kizielewicz et al [22] identified a set of criteria for solving a windfarm location selection problem. Riaz et al [23] introduced a decision support system for sustainable energy planning decision management based on q-rung orthopair fuzzy set (q-ROFS). The proposed approach was applied to a sustainable energy planning problem in Pakistan in order to demonstrate the plan's feasibility and validity.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Kizielewicz et al [22] identified a set of criteria for solving a windfarm location selection problem. Riaz et al [23] introduced a decision support system for sustainable energy planning decision management based on q-rung orthopair fuzzy set (q-ROFS). The proposed approach was applied to a sustainable energy planning problem in Pakistan in order to demonstrate the plan's feasibility and validity.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Riaz et al [48][49][50][51] introduced the concepts of q-rung orthopair fuzzy prioritized aggregation operators, q-rung orthopair fuzzy hybrid aggregation operators, q-rung orthopair fuzzy information aggregation using Einstein operations, q-rung orthopair fuzzy Einstein prioritized aggregation operators with application towards multi-criteria group decision making (MCGDM). Aggregation operators and MCDM methods have been studied by; Xu [52], Xu and Cai [53], Xu [54], Yager [55], Ye [56,57], Zhan et al [58,59], Zhang and Zhan [60,61], Zhang et al [62], and Harrison et al [5].…”
Section: And Degree Of Indefiniteness Is Given By πmentioning
confidence: 99%
“…They also used their proposed methodology for DM, medical diagnoses, and pattern recognition, and developed operational laws, presented some prioritized AOs under the linguistic IFS environment [23], and extended the Maclaurin symmetric mean (MSM) operators to IFSS based on Archimedean T-conorm and T-norm [24]. Riaz et al [25] developed some AOs using Einstein Operations with desirable properties and established a MCDM method to solve DM complications. Faizi et al [26] presented a novel MCDM technique using normalized, interval-valued, triangular fuzzy numbers, and applied it to solve DM complications.…”
Section: Introductionmentioning
confidence: 99%